The Role of Nanomaterials in Modulating the Structure and Function of Biomimetic Catalysts - Huang, Yanyan; Yu, Deshuai; Qiu, Yibin; Chu, Lanlin; Lin, Youhui (Frontiers in Chemistry, 2020)
Nanomaterial-incorporated enzyme mimics have so far been examined in various cases, and their properties are governed by the properties of both catalysts and materials. This review summarizes recent efforts in understanding the role of inorganic nanomaterials for modulating biomimetic catalytic performance. Firstly, the importance of enzyme mimics, and the necessity for tuning their catalysis will be outlined. Based on structural characteristics, these catalysts are divided into two types: traditional artificial enzymes, and novel nanomaterials-based enzyme mimics. Secondly, the mechanisms on how nano-sized materials interact with these catalysts will be examined. Intriguingly, incorporating various nanomaterials into biomimetic catalysts may provide a convenient and highly efficient method for the modulation of activities as well as stabilities or introduce new and attractive features. Finally, the perspectives of the main challenges and future opportunities in the areas of nanomaterial-incorporated biomimetic catalysis will be discussed. In this regard, nanomaterials as a kind of promising scaffold for tuning catalysis will attract more and more attention and be practically applied in numerous fields.